Von der Hoffnung Rechenschaft geben: Linien einer Theologie in Transformation im Gespräch mit den Beiträgen dieses Heftes. - Kirschner, Martin (Münchener theologische Zeitschrift, 2024)
In the article, the author responds to the four essays that take up topics from his theological work. This explains the particular genre of the reflections. First, the approach of a 'theology in transformation' is outlined, which, starting from the contemporary crises, seeks to interpret the signs of the times, develop possible answers and open up perspectives of hope in dialogue and interdisciplinary cooperation. Taking up Markus Riedenauer's critique of 'cybernetism', the article emphasises the political significance of dissent, contradiction and a resistant communicative practice. On the other hand, it points to the necessity of a relational thinking that goes beyond anthropologies of sovereignty. With Jakob Deibl, this points to figures of messianic hope, in which the apocalyptic disruption is combined with a messianic anticipation of salvation to form a 'weak', vulnerable way of thinking and believing. In a conversation with Dirk Ansorge and Anselm of Canterbury, the essay relates such practice to the 'ever greater' God, who, in the self-giving of Jesus on the cross, transforms history from within and leads to a corresponding practice of discipleship. In connection with Margit Eckholt, this corresponds to a performative and transformative, liberating and interculturally oriented theology that is taking shape in a synodal world church. Such a theology remains provisional and, on the way, as a resistant messianic hope in apocalyptic times.